2008
DOI: 10.1093/aje/kwn358
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Complement Factor H Genotypes, Fish Consumption, and Inflammatory Markers on Long-Term Risk for Age-related Macular Degeneration in a Cohort

Abstract: At baseline in 1992-1994, the authors assessed the combined effects of complement factor H (CFH) genotypes with smoking, fish consumption, and inflammatory markers on the risk of age-related macular degeneration (AMD) in 3,654 persons aged > or =49 years. They reexamined 75% of the survivors after 5 and 10 years, confirming incident AMD by side-by-side photographic grading. Of the 2,452 persons followed in the Blue Mountains Eye Study, 1,881 were genotyped (rs1061170), with CC, CT, and TT identified in 13.6%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 68 publications
0
50
1
2
Order By: Relevance
“…Thus, whether the protection offered by these nutrients is sufficient to counteract the genetic risk is unclear. 32,33 Within the framework of the large population-based Rotterdam Study, we explored the relationship between a healthy diet, genetic risk, and early AMD. We assessed the intake of antioxidants, zinc, and -3 fatty acids in daily foods, diagnosed the onset of early AMD during a lengthy follow-up, and investigated the risk-reducing effect of these nutrients in the various genotypes of CFH Y402H and LOC387715 A69S.…”
mentioning
confidence: 99%
“…Thus, whether the protection offered by these nutrients is sufficient to counteract the genetic risk is unclear. 32,33 Within the framework of the large population-based Rotterdam Study, we explored the relationship between a healthy diet, genetic risk, and early AMD. We assessed the intake of antioxidants, zinc, and -3 fatty acids in daily foods, diagnosed the onset of early AMD during a lengthy follow-up, and investigated the risk-reducing effect of these nutrients in the various genotypes of CFH Y402H and LOC387715 A69S.…”
mentioning
confidence: 99%
“…Many studies have provided evidence for a protective role of omega-3 fatty acids supplementation in AMD risk 91,[106][107][108][109][110][111][112][113][114][115][116][117] . The first study evaluating the relationship between dietary fat and AMD was published by Mares-Perlman et al 106 .…”
Section: Omega-3 Long Chain Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…In the Blue Mountains Study group, 1881 participants were genotyped for complement factor H (CFH) genetic variants 117 . Wang et al reported that AMD risk increased with each additional C allele.…”
Section: Omega-3 Long Chain Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…n-3 LC-PUFAs may increase the macular pigment density, which alters blue light penetration and has local antioxidant and anti-inflammatory activities (131). Increased fish and n-3 FA consumption has also been correlated with decreased AMD risk (50,(132)(133)(134)(135). As the primary FA in the retina, DHA helps regenerate rhodopsin, thereby reducing oxidative stress.…”
Section: Introductionmentioning
confidence: 99%